The secrets of El Dorado viewed through a microbial perspective - Briones, Aurelio (Frontiers in Microbiology, 2012)
The formation of the Amazon Dark Earths was a model of sustainable soil management that involved intensive composting and charcoal (biochar) application. Biochar has been the focus of increasing research attention for carbon sequestration, although the role of compost or humic substances (HS) as they interact with biochar has not been much studied. We provide a perspective that biochar and HS may facilitate extracellular electron transfer (EET) reactions in soil, which occurs under similar conditions that generate the greenhouse gases methane and nitrous oxide. Facilitating EET may constitute a viable strategy to mitigate greenhouse gas emission. In general, we lack knowledge in the mechanisms that link the surface chemical characteristics of biochar to the physiology of microorganisms that are involved in various soil processes including those that influence soil organic matter dynamics and methane and nitrous oxide emissions. Most studies view biochar as a mostly inert microbial substrate that offers little other than a high sorptive surface area. Synergism between biochar and HS resulting in enhanced EET provides a mechanism to link electrochemical properties of these materials to microbial processes in sustainable soils.